Nageotte nodules in human dorsal root ganglia reveal neurodegeneration in diabetic peripheral neuropathy - Stephanie I. Shiers; Khadijah Mazhar; Andi Wangzhou; Rainer Haberberger; Joseph B. Lesnak; Nwasinachi A. Ezeji; Ishwarya Sankaranarayanan; Diana Tavares-Ferreira; Anna Cervantes; Geoffrey Funk; Peter Horton; Erin Vines; et al. (Nature Communications)
Abstract Nageotte nodules, first described in 1922 by Jean Nageotte, are clusters of non-neuronal cells that form after sensory neuron death. Despite their historical recognition, little is known about their molecular identity nor their involvement in neuropathies that involve neuronal loss like diabetic peripheral neuropathy (DPN). In this study, we molecularly characterize Nageotte nodules in dorsal root ganglia recovered from organ donors with DPN. Here we show that Nageotte nodules are abundant in DPN sensory ganglia and account for 25% of all neurons. Peripherin-and Nav1.7-positive dystrophic axons invade Nageotte nodules, forming small neuroma-like structures. Using histology and spatial sequencing, we demonstrate that Nageotte nodules are mainly composed of satellite glia and non-myelinating Schwann cells that express SPP1 and are intertwined with sprouting sensory axons originating from neighboring neurons. Our findings suggest that Nageotte nodules are an integral feature of dorsal root ganglion neurodegeneration, providing potential therapeutic targets for sensory neuron protection and pain management in DPN.